Analysis of Factors Affecting Auditor Switching - N Nursiam; Dedy Yana Purwana; Indah Permata Dewi (Riset Akuntansi dan Keuangan Indonesia)
This research aimed to determine the impact of management changes, company growth, financial distress, and the percentage change in ROA, KAP size, and company size on auditor switching. In this study, the management changes and KAP size employed dummy variables. The company growth is projected by its delta revenue percentage; financial distress is projected by its debt to equity ratio (DER); the percentage change in ROA is projected by its delta return on asset (ROA); and the size of the company is projected with the natural logarithm of total assets. This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) from 2017–2019. The sampling technique applied in this study was the purposive sampling technique. The sample in the study was 68 companies, and it was conducted over three years, resulting in 204 data. The employed data analysis technique was logistic regression analysis. The results showed that the variable percentage change in ROA and KAP size affected auditor switching. Meanwhile, the variables of management changes, company growth, financial distress, and company size do not affect auditor switching.